RECRUITMENT AND FAMILY NETWORKS IN MOESIA INFERIOR - PÁZSINT, Annamária – Izabella (Studia Universitatis Babeș-Bolyai Historia, 2023)
The goal of this paper is to bring under scrutiny the cases of connections between civilian families and the Roman army in Moesia Inferior, in order to map the recruitment pattern of the military. For this purpose, I shall first examine the family networks, which point to recruitment and sometimes social mobility over generations; and secondly, I shall also look at those families whose members do not seem to be all active (of the attested sample) in the army. Rezumat: Scopul acestui studiu este să aducă în atenție relația dintre familiile civile şi armata romană din Moesia Inferior pentru a identifica modelele de recrutare ale militarilor. Vor fi examinate rețelele familiale care indică modul de recrutare şi, uneori, mobilitatea socială de-a lungul generațiilor; în al doilea rând, vor fi discutate cazurile acelor familii ale căror membri nu par să fie cu toții implicați în armată. Cuvinte-cheie: armata romană, Moesia Inferior, recrutare, rețele familiale Article: archeology; Received: 12.03.2023; Revised: 16.03.2023 Accepted: 18.03.2023; Available online: 28.04.2023